Analysis of Economic Growth and Poverty Rate in Central Kalimantan During the COVID-19 Pandemic - Tri Lantia br Panjaitan septi panjaitan; Rirys Arisca; Irawan Irawan; Pratiwi Subianto (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Purpose - This study aims to analyze the direct and indirect influence of GRDP PerCapita, High School Participation Rate, Labor Force Participation Rate, andPercentage of Population with Access to Clean Water on Poverty Rate throughEconomic Growth in Central Kalimantan during the 2017-2020 period.Design/methodology/approach - Data analysis using the Path Analysis model.Findings - The results of the study show that: 1) Per Capita GRDP, labor forceparticipation rate, and percentage of the population with access to clean water havea direct positive and significant influence on economic growth in CentralKalimantan. 2). Per Capita GRDP, high school participation rate, labor force participation rate, and percentage of the population with access to clean water havea direct positive and significant influence on the poverty rate in CentralKalimantan. 3). Economic growth has a direct positive and significant influence onthe poverty rate in Central Kalimantan. 4) Per Capita GRDP, High SchoolParticipation Rate, Labor Force Participation Rate, and Percentage of Populationwith Access to Clean Water have an indirect and significant influence on the PovertyRate through Economic Growth in Central Kalimantan.